Environmental persistence of nontyphoidal Salmonella in an urban informal settlement in Nairobi, Kenya - Collins K. Kebenei; David Onyango; Kelvin Kering; Cecilia Mbae; Susan Kavai; Michael Muraya; Celestine Wairimu; Georgina Odityo; Kristin Weber; Michael Pietsch; Tanja Pilz; Oliver Drechsel; et al. (PLoS ONE, 2025)
Non-typhoidal Salmonella (NTS) presents a considerable health threat to children in low-resource settings, where clean water, sanitation, and hygiene are often inadequate. However, the environmental factors influencing NTS persistence and spread remain poorly understood. We utilized a case-control approach to investigate environmental factors associated with NTS infection in children living in Nairobi’s informal settlements between August 2022 and July 2023. Stool samples were collected from febrile children, with or without diarrhea, who visited healthcare facilities. The study included 42 laboratory-confirmed NTS-positive cases and 42 NTS-negative children from the same community. Environmental samples, including drinking water, open drains, soil, and household effluent, were collected from both case and control households, in addition to raw sewage from main sewer-line convergence points. Conventional microbiological culture and quantitative Polymerase Chain Reaction techniques were employed for NTS detection, with genomic sequencing used for strain characterization. Environmental samples from case households showed a higher NTS contamination rate of 33.3% (42/126) compared to control households of 7.2% (9/126). Higher odds of NTS infection in children were associated with household environmental factors, particularly exposure to household effluent (OR = 7.7, 95% CI: 2.18–34.82, p = 0.0005), drinking water (OR = 6.4, 95% CI: 1.57–37.76, p = 0.0055), and soil (OR = 5.4, 95% CI: 1.01–54.28, p = 0.0485). Genomic analysis revealed a common strain, Salmonella Enteritidis ST11, in clinical and environmental isolates. These findings highlight the plausible role of the household environment as a reservoir for NTS, perpetuating infection cycles within the community. Addressing this challenge requires a multifaceted approach, including improved sanitation infrastructure, environmental monitoring, and integrated public health interventions to reduce NTS exposure and transmission in high-risk populations.